Penile ulcer ATRA related in patient with acute promyelocytic leukemia - Irfan Yavasoglu; Mustafa Unubol; Gokhan Sargin; Gurhan Kadikoylu; Zahit Bolaman (Mediterranean Journal of Hematology and Infectious Diseases)